FAKTOR-FAKTOR YANG MENGHAMBAT COMING OUT PADA LESBI FEMME DI BALI - Dewi, I Gst Ayu Puspasari; Tobing, David Hizkia (Jurnal Psikologi Udayana, 2016)
In psychology, lesbian has not regarded as a psychiatric disorder since 1973 until now based on guidebook of the DSM (Diagnostic and Statistical Manual of Mental Disorder). But until now presence of lesbians on the society are still faced with a denial and violation of religion, norms, and values prevailing in society. In Indonesia, especially in Bali, lesbian being as individual mostly "down" due to two main things, there are strong patriarchy culture that makes women as a minority and then because lesbians are still considered a disease and deviant. This makes the lesbian increasingly difficulty in adjusting to society that makes lesbian experience barriers to self-disclosure (coming out). Doing coming out in lesbian is not easy, especially in the lesbian femme which recognized very good at hiding his identity as a lesbian, because other people cannot just interpret a feminine woman is a lesbian. This makes the researchers want to determine the factors that hinder the coming out on lesbian femme in Bali. This study uses qualitative research methods with phenomenology approach. Respondents this study were four people who have an identity as a lesbian femme in Bali and have not done of coming out phase as a lesbian. The results of this study indicate that all respondents have not been able to reach the final stage of coming out as known as integration stage. The respondents only can reach the stage of awareness, exploration and acceptance. There are two limiting factor which inhibit of coming out phase, factors that originate from within the individual (internal limiting factor) and the factors that come from outside the individual (external limiting factor). Internal limiting factor obtained in the research that is the hope of re-heterosexual, guilt, and love, while the external limiting factor is influenced by family, social pressures, norms and culture. Keywords: Inhibit, Self-disclosure, Coming Out, Lesbian, Bali